Policy and practice review consensus statements and clinical guidelines on managing pediatric trauma and orthopedics during the COVID-19 pandemic: a systematic review on the global response for future pandemics and public health crises - Sugand, Kapil; Park, Chang; Aframian, Arash; Gupte, Chinmay M.; Sarraf, Khaled M.; , COVid Emergency Related Trauma and orthopaedics (COVERT) Collaborative (Frontiers in Pediatrics, 2024)
Introduction: The COVID-19 pandemic has been recognized as an unprecedented global health crisis. Over 7 million mortalities have been documented with many paediatric fatalities. Trauma and orthopaedic care, much like other specialities, were marginalized due to resource allocation during the pandemic which affected paediatric care. This is the first systematic review to centralise and compile the recommended published guidelines from professional bodies in principally English speaking countries on managing paediatric trauma and orthopaedic care. These guidelines will be required to be implemented sooner and more effectively in case of future pandemics with similar impact. Methods: A search was conducted on PubMed/MedLine, Cochrane Library and Embase using terms including p(a)ediatric or child* and/or COVID* or coronavirus or SARS-CoV-2 and /or trauma and/or orthop(a)edic* with a simplified MeSH heading [mh] in order to make the search as comprehensive as possible. General terminology was utilized to make the search as exhaustive as possible for this systematic review. Another search was conducted on resources available in the public domain from professional bodies publishing on consensus statements and clinical practice guidelines in countries where English is the principal language managing pediatric trauma and orthopedics. The review adhered to PRISMA guidance. Results: The search revealed a total of 62 results from both databases and professional bodies. Duplicates were removed. This was then reviewed to identify a total of 21 results which fit the inclusion criteria and included within the main analysis. The guidelines from professional bodies were outlined and categorized into aspects of clinical care. Discussion: The impact of COVID-19 pandemic has compelled for changes in clinical practice and pediatric management. The systematic review highlights the relevant guidelines on service provision for pediatric patients including indications for urgent referrals, surgical prioritization, reasons for follow-up and trauma guidelines. The rationale for care during the unpredictable evolution of the COVID-19 pandemic may have the potential to be translated and replicated in future pandemics of similar significance.